The Development of Greek Philosophy and the Middle Ages - Tsabit Maulana; Zaenal Fadhilah (Annujum: Journal of Humaniora and Law, 2025)
The development of ancient Greek philosophy began with the pre-Socratic philosophers who carried a cosmological approach, such as Thales and Anaximander, to the golden age of philosophy led by Socrates, Plato, and Aristotle. Greek philosophy focused on the search for truth through rationality and logic, developing basic concepts such as ethics, metaphysics, and epistemology. Socrates introduced the dialectical method, Plato developed the theory of ideas, and Aristotle formulated a system of logic that became the basis of science. In the Middle Ages, philosophy underwent a transformation under the influence of Christianity. Scholastic philosophy became dominant, with the aim of reconciling faith and reason. Thomas Aquinas became a major figure with his work combining Aristotelian thought with Christian doctrine. This century was marked by an emphasis on theology, metaphysics, and ethics, as well as an attempt to understand the relationship between God and his creation. These developments formed the basis for modern and renaissance philosophy, and have influenced Western thought to this day. The research method in this article is Library research, also known as literature research by collecting and analyzing literature from various sources such as books, scientific journals, and research reports. The sources selected are the most relevant and recent to ensure the accuracy and credibility of the findings. The results of this study are developments In the 6th century BC, philosophy was still in the form of mythology or fairy tales believed by the Greeks. Greek society has a belief system that everything must be accepted as everything that comes from fairy tales or in other words does not rely on reason. In Greece, unlike in other areas, at that time Greece was not bound by caste, not bound by religious beliefs or fixated on thoughts spread by priests, so that intellectually they were freer in their lives. The history of medieval philosophy or known as Medieval or Medioevo began around the 5th century, precisely in 476 where the momentum of the end of the Western Roman Empire, until the 16th century. 7 The term 'middle ages' itself generally refers to the transition period from ancient Greco-Roman times to modern times.